2013
DOI: 10.1186/1687-9856-2013-17
|View full text |Cite
|
Sign up to set email alerts
|

Lower A1c among adolescents with lower perceived A1c goal: a cross-sectional survey

Abstract: BackgroundThe International Society for Pediatric and Adolescent Diabetes (ISPAD) and the American Diabetes Association (ADA) have established a hemoglobin A1c (A1c) target of less than 7.5% for adolescents with type 1 diabetes (T1D). However, many adolescents are unaware of their A1c target, and little data exist on how knowledge of this A1c target affects the actual A1c they achieve. We sought to evaluate the relationship between awareness of the A1c target and the actual A1c achieved in adolescents with T1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 14 publications
9
14
0
Order By: Relevance
“…In this study, 28.1% of children with type 1 DM were found at HbA 1c target. The percentage of children achieving HbA 1c target is consistent with other observational studies based on registry data and randomized clinical trials , confirming that HbA 1c levels are often lower in younger patients.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, 28.1% of children with type 1 DM were found at HbA 1c target. The percentage of children achieving HbA 1c target is consistent with other observational studies based on registry data and randomized clinical trials , confirming that HbA 1c levels are often lower in younger patients.…”
Section: Discussionsupporting
confidence: 88%
“…The Hvidoere study found that differences in glycaemic targets played a significant role in explaining HbA 1c differences between centres [15]. It has also been previously reported that a lower perceived HbA 1c goal is associated with the achievement of lower levels in adolescents with T1D [16]. Thus, it may be more than a coincidence that the proportion of T1DX children meeting the ADA goal of 8.5% (69 mmol/mol) (66%) is close to that of DPV children meeting the 7.5% (58 mmol/mol) ISPAD goal (56%).…”
Section: Discussionmentioning
confidence: 91%
“…Percentage difference in the two preschool cohorts of the German–Austrian Diabetes Patienten Verlaufsdokumenation (DPV)‐Registry and the American Type 1 Diabetes Exchange in achieving the respective hemoglobin A1c (HbA1c) goals that were proposed in Europe (<7.5%) and the USA (<8.5%). The odds for achieving either target were greater in the DPV but the difference was much more pronounced for the lower goal, without any difference in the hypoglycemia rates .…”
Section: Summary Of Recent Findings Leading To Changing the A1c Targementioning
confidence: 87%